Analogycal writings of digitality in contemporary spanish poetry. "Patchwork" and "Carne triste" by Pablo Velasco - Gómez Vegas, Miriam (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article analyzes the scope and characterizations of digitality in contemporary Spanish poetry as a relevant element in its codes and imaginaries. For this purpose, different theoretical contributions belonging to the study of new media, digital art and literature and Affective Studies are examined. We then proceed to the poetic analysis of two works published on paper but decisively crossed by the digital: Patchwork (2019) and Carne Triste (2023) by Pablo Velasco. As will be seen, the digital component endows the poetics with an experimental and avant-garde potential.